Cyber Counseling: Pastoral Support through WhatsApp Group to Fellow Congregants - Kowal, Jeniar Rainhard; Manusiwa, Ceril Maria; Sureni, Sureni; Dendeng, Leonardo Caesar (Proskuneo: Journal of Theology, 2025)
The digital era requires humans to continue to follow and adapt by learning to utilize technology. Likewise, church congregations are required to follow the flow of the times to improve the quality of digital services. Therefore, in the midst of digital developments, the term cyber counseling has emerged which can be used as a pastoral service through WhatsApp Group social media for church congregations. The purpose of this study is to examine and analyze cyber counseling as a tool for providing pastoral support through WhatsApp Group to fellow congregations. This article uses qualitative research with a descriptive nature and collects data through literature studies and then analyzes it to obtain results such as ethical reflection in cyber counseling, the role of WhatsApp Group in pastoral support, practical implementation and mentoring techniques in WhatsApp Group, and cyber counseling offers for today's congregations. Through the results obtained, it can be concluded that cyber counseling through the WhatsApp Group application can convey spiritual messages and guidance, question and answer sessions or open discussions, joint prayers and empathetic support, self-reflection sessions and personal spiritual development, learning through media content